2016
DOI: 10.1371/journal.pone.0162675
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Mechanism of Electromagnetic Field and Thermal Stress on Drosophila melanogaster

Abstract: Temperature is an important factor in research on the biological effects of extremely low-frequency electromagnetic field (ELF-EMF), but interactions between ELF-EMF and temperature remain unknown. The effects of ELF-EMF (50 Hz, 3 mT) on the lifespan, locomotion, heat shock response (HSR), and oxidative stress (OS) of Canton-Special (CS) and mutant w1118 flies were investigated at 25°C and 35°C (thermal stress). Results showed that thermal stress accelerated the death rates of CS and w1118 flies, shortened the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…calculated to be equal to 0.15 W/kg, according to the formula SAR D (s¢E_RMS^2)/r W/kg. A recent publication by Zhang et al 64 concluded that thermal stress weakened the physiologic function and promoted the HSR (Heat Shock Response) and OS (Oxidative Stress) of flies. ELF-EMF aggravated damages and enhanced thermal stress-induced HSP and OS responses.…”
Section: Exposure Conditionsmentioning
confidence: 99%
“…calculated to be equal to 0.15 W/kg, according to the formula SAR D (s¢E_RMS^2)/r W/kg. A recent publication by Zhang et al 64 concluded that thermal stress weakened the physiologic function and promoted the HSR (Heat Shock Response) and OS (Oxidative Stress) of flies. ELF-EMF aggravated damages and enhanced thermal stress-induced HSP and OS responses.…”
Section: Exposure Conditionsmentioning
confidence: 99%
“…The increase in HSP70 mRNA levels after heat and MF exposure was detected also in animal models, such as in transgenic Caenorhabditis elegans nematodes and in Drosophila malanogaster . In C. elegans , 1 h concurrent exposure to 50 and 100 µT under 28 and 29°C thermal stress was carried out ( 56 ) while, in Drosophila , 2 and 24 h concurrent exposures were carried out at 35°C ( 57 ). The potentiation of heat-induced HSP16 ( 56 ) and HSP22 and HSP26 ( 57 ) expression by concurrent MF was detected.…”
Section: Combined Exposure To Elf-mf and Heatmentioning
confidence: 99%
“…The increase in this lipid peroxidation marker was observed after 24-h exposure and remained elevated until 7-day exposure. Zhang et al ( 2016 ) have shown that effect of EMF on MDA levels is sex-dependent. They observed decline in MDA level in male, but not in female Drosophila exposed to EMF (50 Hz, 3 mT) for 12 h. However, in our experiments, the intensity and duration of EMF exposure was higher, what could act as a marked stressor.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, significant changes in levels of antioxidants, such as glutathione, superoxide dismutase or catalase were observed (Kivrak et al 2017 ). Zhang et al ( 2016 ) demonstrated that thermal stress (35 °C) and EMF exposure (50 Hz, 3 mT) elicit a synergistic effect, strengthening the negative effect of EMF on lifespan, locomotion and oxidative stress in Drosophila melanogaster .…”
Section: Introductionmentioning
confidence: 99%